Islamic Philanthropic Solution In Handling The Economy During Pandemic Covid-19 Indonesia - Syarifuddin, Syarifuddin; Akramunnas, Akramunnas; Iswandi, Heri; Raya, Muhammad Yaasiin; Basri, Ade Darmawan (Jurnal Iqtisaduna, 2020)
COVID-19, globally reported as much as 15,665,350, died as many as 638,169 recovered as many as 8,982,020, for Indonesia case COVID 19 reported as much as 95,418, died as much as 4,665 recovered as many as 53,945, and South Sulawesi case 19 reported as much as 8,612, died as much as 290 recovered as much as 5,675. Even predicted this case will still happen spike again. Of course, this will cause an impact on the economy in Indonesia. The purpose of this research is to offer Islamic philanthropy solutions during Covid-19 pandemic in Indonesia. This study uses document studies with a literature approach review. The results of this study showed that the Islamic philanthropy solution in dealing with the impact of pandemic Covid-19 There were two solutions to the Islamic Philanthropy Management System (ZISWAF) namely the first, one-way management system. In this system the accepted Community funds are distributed simultaneously to the community with a scale of micro-economic priorities. Second, the feed back management system, the distribution feedback management system with mudharabah muqayyadah (a financing product with entrusted entrepreneurs to manage funds with a profit sharing system in order to increase the benefits received by mustahik)